Предмет: Алгебра,
автор: hfoshf
Упростите выражение: (a-1/a^2)*(ax-a/a-1)+(1-x/2a) выражение в скобочках - это типо дробь))
Ответы
Автор ответа:
0
(a-1)/a² * (ax-a)/(a-1)+(1-x/2a) = (a-1)*a(x-1)/a²(a-1)+(1-x/2a)= (x-1)/a+(1-x)/2a =
= (2x - 2 + 1 - x)/2a = (x-1)/2a
Автор ответа:
0
(а-1/a^2)*(ax-a/a-1)+(x-1/2a)=((a-1)*a(x-1)/a^2*(a-1))+((1-x)/2a)=((x-1)/a)+((1-x)/2a)=
=((2x-2)/2a)+((1-x)/2a)=((2x-2+1-x)/2a)=x-1/2a
"/"-дробь
Похожие вопросы
Предмет: Русский язык,
автор: malkv6607
Предмет: История,
автор: alenaeev22a
Предмет: Математика,
автор: zaurtoktaganov
Предмет: Физика,
автор: zhakalek